Immature dendritic cells derived exosomes promotes immune tolerance by regulating T cell differentiation in renal transplantation - Pang, Xin-Lu (Aging (Albany NY), 2019)
Objective: To investigate the mechanism of immature dendritic cells-derived exosomes (imDECs) in the regulation of T cell differentiation and immune tolerance in renal allograft model mice. Results: imDECs significantly improved the percent of survival, relieved inflammatory response, and reduced CD4+T cell infiltration. In addition, imDECs reduced the rejection associated cytokines in allograft mice, and increased the percentage of Foxp3+CD4+T cells in spleen and kidney tissues. imDECs suppressed the IL17+CD4+T cells and promoted the Foxp3+CD4+T cells under Th17 polarization condition. Moreover, miR-682 was found to be highly expressed in imDECs which suppressed the IL17+CD4+T cells and promoted the Foxp3+CD4+T cells. Luciferase reporter assay showed ROCK2 was a target of miR-682, and ROCK mRNA level was negative correlated with miR-682 mRNA level. Conclusion: miR-682 was highly expressed in imDECs, and imDECs-secreted miR-682 promoted Treg cell differentiation by negatively regulating ROCK2 to promote immune tolerance in renal allograft model mice. Methods: Renal allograft model mice were established, and imDECs or mature dendritic cells-derived exosomes (mDECs) were injected into model mice. Rejection associated cytokines IFN-γ, IL-2, IL-17 levels in plasma were detected by ELISA. IL-17A, Foxp3, miR-682, ROCK2, p-STAT3, p-STAT5 expressions were measured by qRT-PCR or western blot.